Smoking status and tumor necrosis factor-alpha mediated systemic inflammation in COPD patients - Tanni, Suzana E. [UNESP]; Pelegrino, Nilva R. G. [UNESP]; Angeleli, Aparecida Y. O.; Correa, Camila; Godoy, Irma de [UNESP] (Biomed Central Ltd., 2010)
Background: Smoking cause airway and systemic inflammation and COPD patients present low grade inflammation in peripheral blood. However, data on the influence of smoking itself on systemic inflammation in COPD patients are scarce. This study investigated the association between inflammation, smoking status, and disease.Methods: A cross-sectional analysis comparing 53 COPD ex-smokers, 24 COPD current smokers, 24 current smoker controls and 34 never-smoker controls was performed. Assessments included medical history, body composition, spirometry, and plasma concentration of tumor necrosis factor-alpha (TNF-alpha), interleukins (IL)-6, IL-8, and C-reactive protein (CRP).Results: Our exploratory analysis showed that serum TNF-alpha was higher in COPD current smokers [4.8(4.2-5.8)pg/mL] and in current smoker controls [4.8(4.2-6.1)pg/mL] when compared to COPD ex-smokers [4.3(3.9-4.9)pg/mL; p = 0.02] and to never-smoker controls [3.7(3.4-4.0)pg/mL; p < 0.001]. Multiple regression results with and without adjustment for covariates were consistent with the hypothesis that TNF-alpha levels were associated with smoking status in both models (p < 0.001 and p < 0.001). IL-6 and CRP were significantly higher in COPD patients when compared to smoker and never-smoker controls and the multiple regression analysis confirmed the association of these mediators with disease, but not with smoking status (p < 0.001 and p < 0.001). IL-8 had only a borderline association with disease in both models (p = 0.069 and p = 0.053). No influence of disease severity, inhaled corticosteroid, fat-free mass (FFM) depletion and long term oxygen therapy (LTOT) use on systemic inflammation was found.Conclusion: Smoking may influence TNF-alpha mediated systemic inflammation, which, in turn, may account for some of the benefits observed in patients with COPD who stop smoking.